TRoponin of Unknown origin in STroke evaluated by multi-component cardiac Magnetic resonance Imaging – The TRUST-MI study - Mengel, Annerose; Nenova, Lilyana; Müller, Karin A. L.; Poli, Sven; Kowarik, Markus C.; Feil, Katharina; Mizera, Lars; Geisler, Tobias; Kübler, Jens; Mahrholdt, Heiko; Ernemann, Ulrike; Hennersdorf, Florian; et al. (Frontiers in Cardiovascular Medicine, 2022)
Aims: Increased high-sensitive cardiac troponin I (hs-cTnI) levels are common in patients with acute ischemic stroke. However, only a minority demonstrates culprit lesions on coronary angiography, suggesting other mechanisms, e.g. inflammation, as underlying cause of myocardial damage. Late Gadolinium Enhancement (LGE)-cardiac magnetic resonance (CMR) with mapping techniques (T1, T2, extracellular volume (ECV)) allow the detection of both focal and diffuse myocardial abnormalities. We investigated the prevalence of culprit lesions by coronary angiography and myocardial tissue abnormalities by a comprehensive CMR protocol in troponin-positive stroke patients. Methods and results: Patients with troponin-positive acute ischemic stroke and no history of coronary artery disease were prospectively enrolled. Coronary angiography and CMR (LGE, T1+T2 mapping, ECV) were performed within the first days of the acute stroke. Twenty-five troponin-positive patients (mean age 62 years, 44% females) were included. 2 patients (8%) had culprit lesions on coronary angiography and underwent percutaneous coronary intervention. 13 patients (52%) demonstrated LGE: (i) n=4 ischemic, (ii) n=4 non-ischemic, (iii) n=5 ischemic AND non-ischemic. In the 12 LGE-negative patients, mapping revealed diffuse myocardial damage in additional 9 (75%) patients, with a high prevalence of increased T2 values. Conclusions: Our data show a low prevalence of culprit lesions in troponin-positive stroke patients. However, >50% of the patients demonstrated myocardial scars (ischemic + non-ischemic) by LGE-CMR. Mapping revealed additional myocardial abnormalities (mostly inflammatory) in the majority of LGE-negative patients. Therefore, a comprehensive CMR protocol gives important insights in the etiology of troponin which might have implications for the further work-up of troponin-positive stroke patients.